2014
DOI: 10.1179/2042618613y.0000000064
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between various anatomical landmarks used for localizing the first rib during surface palpation

Abstract: This study confirms the anatomical accuracy and feasibility of using the C1 TP span to determine the general width of the T1 TP span while palpating for the first rib just lateral to the T1 TP. Additionally, this study demonstrates that the more easily palpated mastoid process serves as an effective landmark to identify a width sufficiently lateral to the T1 TP, appropriate for first rib palpation through the trapezius muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…In this study, palpation of first rib and assessment of accessory movements reached a strong consensus of being key aspects to identify the first rib dysfunction. The longitudinal caudad accessory movement claims to assess first rib passive mobility [26]; however, its reliability has been questioned when used for detecting passive stiffness of the first rib [27]. Loyd et al [26] suggested a method to locate the first rib that was valid, but only on a cadaver.…”
Section: Cervical Rotation Lateral Flexion Test-reliability/validitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, palpation of first rib and assessment of accessory movements reached a strong consensus of being key aspects to identify the first rib dysfunction. The longitudinal caudad accessory movement claims to assess first rib passive mobility [26]; however, its reliability has been questioned when used for detecting passive stiffness of the first rib [27]. Loyd et al [26] suggested a method to locate the first rib that was valid, but only on a cadaver.…”
Section: Cervical Rotation Lateral Flexion Test-reliability/validitymentioning
confidence: 99%
“…The longitudinal caudad accessory movement claims to assess first rib passive mobility [26]; however, its reliability has been questioned when used for detecting passive stiffness of the first rib [27]. Loyd et al [26] suggested a method to locate the first rib that was valid, but only on a cadaver. More research is indicated to support the use of this procedure.…”
Section: Cervical Rotation Lateral Flexion Test-reliability/validitymentioning
confidence: 99%
“…The examination is repeated for the contralateral side and also for D2. To successfully evaluate the cost-transverse joint, a line branching off perpendicularly from the mastoid process towards the rib tubercle has to be imaged; the joint is located medially to this line [38]. This joint can generate pain, thanks to the presence of neuropeptides which communicate with the somatic and autonomic system (Substance P, calcitonin-gene-related peptide, neuropeptide Y) [39].…”
Section: First Phase: the Patient Standingmentioning
confidence: 99%
“…Once the first rib is detected by using thumbs, the rib must be pushed caudally pushing, to verify its elasticity; otherwise, always by using thumbs, the operator can verify if one rib is more raised than the contralateral one in inspiration, by asking for deep inspirations (the first rib raised), and expirations (the first rib lowers) [38]. The movement is known as the bucket handle [37] [38]. A positional alteration is a frequent cause of TOS [38].…”
Section: The Third Phase: the Patient Being Supinementioning
confidence: 99%
See 1 more Smart Citation